128k views
0 votes
Given f (x) = 3 x minus 1 and g (x) = 2 x minus 3, for which value of x does g (x) = f (2)?

x = three-halves
x = 2
x = five-halves
x = 4

User DsD
by
4.8k points

2 Answers

3 votes

Answer:

x=4

Explanation:

so I plugged in each answer to find which would make g(x)=f(2)

for f(2) you get f(2)= 3(2) -1

f(2)= 6-1 so f(2) is 5

using that plug in each answer into the G equation to get 5 out of it. i used 4

g(4)= 2(4) -3

g(4)= 8-3

g(4)=5

ta da the answer is x=4

hope this is helpful

User Wang Tuma
by
5.7k points
5 votes

Answer:

X = there and halve

3(1/2)

Explanation:

F(x) =3x -2

g(x )= 2x-3

F(2) = 3(2) - 2

= 6-2

= 4

So the value of x that can make g(x) = 4

4= 2x-3

7 = 2x

X= 7/2

X = 3 1/2

User Pavlo Naumenko
by
5.3k points